Evidence of transverse magnetospheric field line oscillations as observed from Cluster and ground magnetometers - Sinha, Ashwini K.; Yeoman, T.K.; Wild, J.A.; Wright, D.M.; Cowley, S.W.H.; Balogh, A. (My University, 2005)
The dynamic spectrum of ULF waves from magnetic field data obtained by the elliptically orbiting Cluster satellites (with an apogee of 119000km, perigee of 19000km and the orbital period of 57h) have been prepared in the frequency range 0 to 120mHz when the satellite was near its perigee. The existence of field line oscillations, with increasing frequency in the inbound sector and decreasing frequency in the outbound sector, is seen in the transverse components, indicating the presence of independently oscillating local magnetic flux tubes in the form of transverse standing Alfvén waves. The results show that toroidal and poloidal modes are excited simultaneously. The analysis of simultaneous ground magnetometer data at the footprint of the satellite suggests that these modes are also excited due to coupling to magnetospheric waveguide modes. The clear signature of a resonant fundamental mode is seen in the ground data whereas Cluster detects a harmonic of this frequency. Lower frequency modes indicative of waveguide oscillations are seen in both the ground data and the compressional field at Cluster.
Keywords: Magnetospheric field; Ground magnetometers; Magnetosphere Ionosphere; ULF waves; Alfvén waves; MHD instabilities